Analysis of Workers' Compliance with Occupational Safety and Health (K3) Protocols: Qualitative Descriptive Study of Mining Workers at Pt. Tonasa Cement - Alya Musfirah Rafiuddin; Andi Jam’an; M.Yusuf Alfian Rendra Anggoro (Pustaka Digital Indonesia, 2026)
The urgency of this research is to examine how organizational culture and ethical literacy influence the integrity of Generation Z human resources through self-control, in response to the growing ethical challenges faced by young workers in the digital era and the increasing need for a trustworthy and sustainable workforce in Bima City. This study examines the influence of organizational culture and ethical literacy on the integrity of Generation Z human resources, with self-control serving as a mediating variable in the context of Bima City, Indonesia. In the era of rapid digital transformation, integrity has become an essential factor in maintaining ethical behavior, accountability, and organizational sustainability among younger generations entering the workforce. This research employs a quantitative approach using a survey design and Structural Equation Modeling–Partial Least Squares (SEM-PLS) for data analysis. Data were collected from 100–200 Generation Z respondents aged 15–25 through purposive sampling using online questionnaires based on a five-point Likert scale. The findings reveal that ethical literacy has a positive and significant effect on integrity, while self-control also significantly strengthens integrity. Organizational culture does not directly influence integrity; however, it significantly affects self-control, indicating an indirect relationship through mediation. In contrast, ethical literacy does not significantly influence self-control. The model demonstrates strong explanatory power, with R-square values of 0.642 for self-control and 0.755 for integrity. These findings suggest that internal psychological factors, particularly ethical literacy and self-control, play a more dominant role than external organizational factors in shaping the integrity of Generation Z. This study contributes to the literature on organizational behavior and human resource management by integrating external and internal determinants of integrity within a comprehensive mediation framework in a local socio-cultural context.